Performance Characteristics of a Rapid Severe Acute Respiratory Syndrome Coronavirus 2 Antigen Detection Assay at a Public Plaza Testing Site in San Francisco. (4th January 2021) - Pilarowski, Genay; Lebel, Paul; Sunshine, Sara; Liu, Jamin; Crawford, Emily; Marquez, Carina; Rubio, Luis; Chamie, Gabriel; Martinez, Jackie; Peng, James; Black, Douglas; Wu, Wesley; et al.
Abstract: We evaluated the performance of the Abbott BinaxNOW rapid antigen test for coronavirus disease 2019 (Binax-CoV2) to detect virus among persons, regardless of symptoms, at a public plaza site of ongoing community transmission. Titration with cultured severe acute respiratory syndrome coronavirus 2 yielded a human observable threshold between 1.6 × 10 4 -4.3 × 10 4 viral RNA copies (cycle threshold [Ct], 30.3–28.8). Among 878 subjects tested, 3% (26 of 878) were positive by reverse-transcription polymerase chain reaction, of whom 15 of 26 had a Ct <30, indicating high viral load; of these, 40% (6 of 15) were asymptomatic. Using this Ct threshold (<30) for Binax-CoV2 evaluation, the sensitivity of Binax-CoV2 was 93.3% (95% confidence interval, 68.1%–99.8%) (14 of 15) and the specificity was 99.9% (99.4%–99.9%) (855 of 856). Abstract : This study examines the utility of the Abbott BinaxNOW rapid direct antigen severe acute respiratory syndrome coronavirus 2 in the context of community screening at a public transit hub, in comparison with reverse-transcription polymerase chain reaction.